The effect of T-stress on the fracture of brittle rock under compression. (October 2015) - Tang, S.B.
Abstract: Crack initiation in rock subjected to compressive loading is analyzed using linear elastic fracture mechanics (LEFM). The resulting theoretical model clarifies the influence of the confining pressure, the presence of friction on the flaw surface and the non-singular stresses ( T -stresses) both parallel ( T x ) and perpendicular ( T y ) to the crack plane on crack initiation. The modified maximum tangential stress criterion is used to determine the crack initiation angle of tensile cracks. Furthermore, an extension of the maximum shear stress criterion is proposed in which the direction and stress level of crack initiation are determined by the magnitude of the maximum shear stress. The critical radius ( r c ) in rock is suggested to be much larger than that in many other engineering materials like glass, metals or polymers. This difference explains why shear fracture is experimentally observed in rock but not in glass or poly (methyl methacrylate) (PMMA). Shear crack initiation becomes more likely with increasing friction and confine pressure. The results suggest that the crack type that predominates depends on the values of friction, confine pressure, flaw inclination angle and the ratio of shear to tensile strength. Highlights: Both parallel and perpendicular T -stresses affecting the crack initiation in rock. The great value of critical radius in rock is the main reason for shear crack. Friction on crack surface results in the transition of tensile to shear failure. The crack type depends on friction, confine pressure, flaw inclination angle and σ c / τ c .